MANUSIA DI TENGAH PANDEMI COVID-19 DALAM PERSPEKTIF DAOISME Refleksi Filosofis Prinsip Wu Wei atas Krisis Kemanusiaan di Tengah Pandemi Covid-19 - Anjelinus Loi (Aggiornamento, 2021)
The focus of this paper is to offer as well as explore Wu Wei's wisdom principles as a way of life to find human harmony in himself and others amid the Covid-19 pandemic. The current disaster, especially the Covid-19 virus, which has a bad impact makes humans worry about its existence. Therefore, humans need a "value" as a principle to guide their life. Thus the author offers Wu Wei's wisdom in the light of Daoism as a way for humans to deal with this Covid-19 pandemic situation. The findings of this paper are that by behaving, human Wu Wei can create a harmonious and peaceful social life in the midst of this disaster. Wu Wei's wisdom invites humans to take the least possible action, and also act according to the objective conditions that are the essence of the existing problems, or what is known as acting naturally. The author thinks the values of Wu Wei Daoism have become actual in the midst of the Covid-19 pandemic situation. The thing is that the development of science and technology leads to "progress" as well as "uncertainty". The author reflects Wu Wei's wisdom in the light of Daoism, inviting people to act appropriately. The fact is that excessive artificiality has proven to have resulted in the degeneration of human dignity today. In this paper, the writer uses the methodology of literature study in the Book of Dao De Jing.